2020
DOI: 10.2147/dddt.s248823
|View full text |Cite
|
Sign up to set email alerts
|

<p>Sinomenine Attenuates Acetaminophen-Induced Acute Liver Injury by Decreasing Oxidative Stress and Inflammatory Response via Regulating TGF-β/Smad Pathway in vitro and in vivo</p>

Abstract: Introduction: Liver disease is common and often life-threatening. Sinomenine (SIN) is an active ingredient extracted from Sinomenium acutum. This study investigated the protective effect and mechanism of sinomenine (SIN) on acetaminophen (APAP)-induced liver injury from in vitro and in vivo. Methods: In vivo experiments, mice were randomly divided into six groups (n=10): control group, model group, SIN (25 mg/kg) group, SIN (50 mg/kg) group, SIN (100 mg/kg) group and SIN (100 mg/kg) + SRI-011381 group. Alanine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Smad protein is the downstream transmembrane receptor of TGF-β and is an important regulatory molecule of TGF-β superfamily signaling [48]. Oxidative stress can induce MMPs and pro-inflammatory cytokines in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Smad protein is the downstream transmembrane receptor of TGF-β and is an important regulatory molecule of TGF-β superfamily signaling [48]. Oxidative stress can induce MMPs and pro-inflammatory cytokines in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Sinomenine (CAS: 115-53-7) is a pure alkaloid that was originally extracted from the Chinese herb, Sinomenium acutum (Rehder and Wilson) of the Menispermaceae family ( 12 ). Sinomenine hydrochloride (SIN) is a hydrochloride form of sinomenine that has attracted the interest of researchers due to its reported safety and potent anti-inflammatory and immunoregulatory effects both in vitro and in vivo ( 13 , 14 ). It has been reported that SIN demonstrated notable therapeutic efficacy for treating collagen-induced arthritis in a rat model ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, SIN can increase the levels of GSH-Px and SOD, reduce the production of MDA, enhance the resistance to oxidative stress and the defense function of cell membranes. 43,44 According to the experimental results, SIN had a good scavenging rate on DPPH radicals in the concentration range of 0.025 to 0.125 mg/mL, and with an IC 50 of 0.084 mg/mL; 0.2 to 0.6 mg/mL of SIN had a good scavenging rate for H 2 O 2 , and the IC 50 was 0.3771 mg/mL. The ability of antioxidants to scavenge radicals depends on the ability of hydroxyl groups to provide hydrogen ions (H + ).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo , SIN can increase the levels of GSH-Px and SOD, reduce the production of MDA, enhance the resistance to oxidative stress and the defense function of cell membranes. 43,44…”
Section: Discussionmentioning
confidence: 99%